THE ROLE AND FUNCTIONS OF THE NOTARY IN THE PROCESS OF HOUSE OWNERSHIP LOANS AT THE BANK AS AN EFFORT FOR ASSET SAFETY AND CLARITY OF LEGAL STATUS (Case Study at Bank BTN Malang Branch Office) - Risdiyanto, Aries Dwi (Universitas Islam Malang, 2022)
The need for a place to live, namely a house is very much needed by humans in their life. The house serves as a place to gather and communicate for the family. The ability in the economy makes it a consideration for every family to build or buy a residential house. Home Ownership Loans (KPR) are long-term loans provided by banks in collaboration with developers to make it easy for consumers to own their own homes by paying installments to the bank. Every financing or credit has a fairly high risk of default. The formulation of the problems to be discussed are: (1) What is the role and function of the Notary in the KPR process at BTN Malang? (2) What are the efforts for asset safety and clarity of legal status made by a notary?The type of research that will be used by the author is empirical juridical research. Data analysis was carried out in a qualitative descriptive manner. The problem approach uses a conceptual and statutory approach. By utilizing primary and secondary data obtained in the field through interviews and document studies.The results of this research are the role and function of the notary in terms of mortgage agreements, namely the notary acting as a public servant because he is appointed by the government to serve the community's needs for valid legal documents. Efforts for safety assets carried out by a Notary in a Home Ownership Credit (KPR) agreement by the State Savings Bank (BTN) Malang Branch, including making a Deed of Authorization to Sell, a Certificate of Imposing Mortgage Rights (SKMHT), and if a default debtor occurs, then Bank BTN Malang Branch submit an application to the Notary/PPAT to increase the Certificate of Imposing Mortgage Rights (SKMHT) to the Deed of Granting Mortgage Rights (APHT), which is then registered by the Notary/PPAT at the Land Office for the issuance of Mortgage Certificates. Keywords: Notaries, Mortgages, Bankin